Raman spectroscopy as an analytical tool for melanoma research. (July 2014) - Brauchle, E.; Noor, S.; Holtorf, E.; Garbe, C.; Schenke‐Layland, K.; Busch, C.
Summary Background Raman spectroscopy is an optical noninvasive screening technology that generates individual fingerprints of living cells by reflecting their molecular constitution. Aim To discriminate melanoma cells from melanocytes, to identify drug‐induced melanoma cell death stages (apoptosis, necrosis, autophagy) and to assess the susceptibility of melanoma cells to anticancer therapy. Methods We used Raman spectroscopy on normal and melanoma cells, and on wild‐type (WT) and mutant melanoma cells, to investigate whether the technique could distinguish between different types of cells, identify mutations and evaluate response to anticancer therapy. Results Using the multivariate principal component analysis of the Raman spectra, melanocytes could be distinguished from melanoma cells, and WT melanoma cells could be distinguished from melanoma cells with BRAF or NRAS mutations. When we used the apoptosis inducer staurosporine, the necrosis inducer 3‐bromopyruvate and the autophagy inducer resveratrol to induce cell death in SKMEL28 melanoma cells, Raman spectroscopy clearly distinguished between these three types of cell death, as confirmed by immunoblotting. Finally, the technique could discriminate between different melanoma cell lines according to their susceptibility to high‐dose ascorbate. Conclusions Raman spectroscopy is a powerful noninvasive tool to distinguish between melanocytes and melanoma cells, to analyze the specific type of cell death in melanoma cells, and to predict the susceptibility of melanoma cells to anticancer drugs.